PROGRAM PEMBERDAYAAN WANITA USAHA KECIL DAN JASA DI DESA KEMAWI KECAMATAN SUMOWONO KABUPATEN SEMARANG - Nina Indriyawati, MNS.; Sugih Wijayanti; Arwani Arwani; Supriyadi Supriyadi (Jurnal LINK, 2016)
The livelihoods of the population in villages Kemawi, Sumowono District, Subdistrict Semarang in general are still working in agriculture, which is in line with the potential of Semarang district still largely an agricultural land. Based on the results of field identification and focus group discussions with 20 members who joined the advisory group concluded that the group wants to develop excellent products in Kemawi which could become an icon and a souvenir for visitors attractions Klenting Grojokan Yellow. FGD results be obtained that the group will develop diversify local materials ie vegetables and alvokado be pickled vegetables, candied vegetables, rice, grilled vegetables, tofu vegetable meatballs, chili alvokado, pancakes alvokado and drink a cup. Tentanng and improving the packaging, labeling, marketing, business management, financial management, and the port on. Results of assistance in getting that formed women's groups in the village Kemawi businesses and groups understand the benefits of packaging, labeling, marketing, business management, financial management, and the pirt.